Phitoremidiation of Combination Pistia Stratiotes and Eichhornia Crassipes Towards Changes in Waste Liquid Waste Changes and Plant Morphological Structure - Endah Rita Sulistya Dewi; Nur Kayati; Maria Ulfah (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Tofu liquid waste tofu contains a low pH of 3 (acidic), because in the manufacturing process there is the addition of a prickly heat, it will cause pollution. One of the efforts to minimize pollution is by doing phytoremediation by combining Pistia stratiotes and Eichornia crassipes. The purpose of this study was to determine the effect of phytoremediation Pistia stratiotes and Eichornia crassipes on changes in pH and plant morphology. Methods: The method used was an experiment with four treatments and three replications by combining 0 g (control) biomass (P0), 75 g Pistia stratiotes and 25 g Eichhornia crassipes (P1), 50 g Pistia stratiotes and 50 g Eichhornia crassipes (P2), and 25 g of Pistia stratiotes and 75 g of Eichhornia crassipes (P3) which will be phytoremediated into four liters of waste with a concentration of 25%. The experimental data were processed by analysis of variance at the 5% level. Results: The results showed that the four treatments were able to increase the pH value of tofu liquid waste for P1 with an average of 6.0 while P0, P2 and P3 had an average pH of 5.7. Conclusions: The morphological structure that showed the best results was P3 with green leaves and stems.